FESTIVAL HERITAGE OMED-OMEDAN SEBAGAI DAYA TARIK WISATA DI SESETAN, DENPASAR - Didik Roy Mahardika, I Wayan (Jurnal Master Pariwisata (JUMPA), 2015)
Despite its natural beauties, Bali is also well-known for its traditional cultures which can attract many tourists to come. Along with the development of tourism, traditional cultures are performed as tourist attractions. This article analyses the development of omed omedan thug of war in Banjar Kaja, Sesetan Village, Denpasar, as atourist attraction. This tradition has been praticed for many decades yet since 2009, the community adopted it as “Sesetan Heritage Omed-omedan Festival” (SHOOF) with two aims, that is to support the Denpasar as “city of cultural” and to perform the tradition in a more professional festival thus not only to maintain the pride of young generation of the local community to preserve their tradition, but also as a unique tourist attraction in an urban setting. Survei was coducted to get perception of both local people and visitors who watch the festival. The article concludes that Sesetan Heritage Omed-omedan Festival has a great potential to develop as a cultural icon for Denpasar tourism. However, to make it a more an attractive event for visitors management improvement is required.